LITERASI KEUANGAN, EFIKASI DIRI, DAN PERILAKU KREDIT ONLINE BERISIKO DI KALANGAN MAHASISWA KOTA BATAM - Rizki Fadhel; Maria Yosefina Meinadia Sekar Kinanti Aswirawan; Hasra Hijratul Adha; Muhammad Jufri; Stevian Mustofa (Journal Publicuho, 2024)
This study aims to analyze the relationship between financial literacy, financial self-efficacy, and risky online credit behaviour among college students in Batam City. The issue of online consumer credit for students has garnered considerable academic attention; however, the mechanisms linking financial literacy to risky credit behaviour are not yet fully understood. A sample of 190 students in Batam City was randomly selected as study respondents. Data were collected through questionnaires and analyzed using SEM-PLS analysis. The findings reveal that students' financial literacy has a positive and significant impact on risky credit behaviour, with subjective financial literacy exerting a stronger influence than objective financial literacy. Additionally, financial literacy positively affects financial self-efficacy. The study also shows that financial self-efficacy partially mediates the relationship between financial literacy and risky credit behaviour. These findings hold implications for policy recommendations aimed at improving financial literacy and enhancing students' understanding of sound financial management practices.